Analysis of capital formation and foreign aid nexus in Nigeria. Issue 2 (11th December 2018) - Orji, Anthony; Ogbuabor, Jonathan E.; Anthony-Orji, Onyinye Imelda; Mbonu, Chibudem O.
Abstract : Purpose: The issue of foreign aid has continued to gain renewed economic cum political attention in the early years of the twenty-first century. At a summit, popularly known as the Millennium Summit, which took place in 2000, there was an agreement by the international community concerning some goals known as the Millennium Development Goals which were targeted to be reached by the year 2015 but have now been replaced by the Sustainable Development Goals. Against this background, it becomes pertinent to ascertain the contributions and impact of foreign aid in the form of Overseas Development Assistance (ODA) on capital formation in Nigeria. This is an area of foreign aid studies that has been ignored by many researchers. Most studies are seen delving into analyzing the aid-growth nexus without evaluating the transmission link through which foreign aid transmits to affect economic growth. There is paucity of studies on the aid-capital nexus. The paper aims to discuss these issues. Design/methodology/approach: The empirical method used was autoregressive distributed lag (ARDL) model. Findings: The empirical results from the ARDL model estimations show that foreign aid, which is proxied by ODA, has a positive and significant impact on capital formation in Nigeria for the years under analysis. The result of the Granger causality test shows that a bi-directional granger causality exists between foreign aid and gross fixed capital formation (GFCF). Originality/value: Empirical results from the ARDL model estimations show that foreign aid, which is proxied by ODA, has a positive and significant impact on capital formation in Nigeria for the years under analysis. The result of the Granger causality test shows that a bi-directional Granger causality exists between foreign aid and GFCF. It is therefore recommended that government should make serious efforts toward the implementation and effective utilization of foreign aid. Appropriate policy measures that would monitor the maximum and effective utilization of foreign aid are also required.